Zur Biologie und Populationsdynamik von Mayetiola destructor (Say, 1817) Kieffer, 1896 an Roggen in Mecklenburg (Diptera: Cecidomyiidae). - Stelter, Helmut; Rothacker, Dietrich; Bielka, F. (Contributions to Entomology = Beiträge zur Entomologie, 1990)
Mayetiola destructor appears regularly, but generally with a low density, in Central Europe on fields cultivated with its host plants. Mass increases of its populations over a period of two or at most three years may be expected at intervals of 15 to 30 years. On drilled fields the crops will rarely be measurably reduced even during such a period, while crops of single plants (in breeding) can be injured.